Resposta imunológica de Alabama argillacea (Hubner) (Lepidoptera : Noctuidae) e de seu predador Podisus nigrispinus (Dallas) (Hemiptera : Pentatomidae) frente a produtos à base de Bacillus thuringiensis Berliner - OLIVEIRA, Andresa Cristina Batista de (2011)
The insects’ midgut pH has a great influence on the activity of Cry toxins. Some toxins are activated under alkaline or acidic conditions. The proteolytic processing of Cry toxins is a crucial step in their activation and information about distribution and interaction of these toxins on target and non-target insects are important to explain how proteolytic activity of digestive enzymes contributes to the tolerance of natural enemies to Cry toxins. Furthermore, studies have shown that insects can adapt to Bacillus thuringiensis (Berliner) toxins under field and laboratory conditions. Because Alabama argillacea (Hübner) (Lep.: Noctuidae), is a monophagous species with short life cycle, it poses a risk of developing resistance to the toxins of B. thuringiensis . The knowledge about the different mechanisms of resistance to these toxins is important to extend the usefulness of commercial products based on Bt. The proteinase activity of the digestive tract of Podisus nigrispinus (Dallas) (Hem.: Pentatomidae), proteolytic capacity of these on Cry1Ac and cellular and humoral immune response of larvae of A. argillacea towards commercial formulations based on B. thuringiensis, were tested. The results indicated that the major enzymes of the digestive tract of P. nigrispinus are serine-proteases and cysteine proteases that work in a neutral to mildly acidic pH and apparently digestive enzymes were not able to process the Cry1Ac toxin within 12 hours of incubation. 4th instar larvae of A. argillacea do not have potential to develop tolerance to Bt formulated based on immunological responses. Dipel® led to quantitative variation in all cell types while XenTari® changed prohemocytes, plasmatocytes, granulocytes and oenocytoids. In insects treated with Dipel® was no increase in the level of nitric oxide. Differences in responses to treatments can be attributed to different composition of the insecticides, Dipel ® had a more effective and faster to control A. argillacea.